Small Bowel Review - Part I - ABR Thomson; E Jarocka-Cyrta; J Faria; GE Wild (Canadian Journal of Gastroenterology)
The small bowel has undergone intense study. Part I of this two-part review of the small bowel focuses on gastrointestinal peptides; intestinal infections and human immunodeficiency virus; drugs; intestinal growth - mucosal proliferation and differentiation; nucleic acids, nucleotides and nucleosides; vitamins and minerals; Whipple's disease; radiation; and early development.